Pengaruh Total Asset Turnover, Debt To Asset Ratio, Current Ratio Terhadap Price To Book Value Melalui Return On Asset Pada Perusahaan LQ45 Periode 2019-2023 - Putri Rahmayani; Desi Ika (Journal of Innovative and Creativity, 2025)
This research aims to determine the Total Asset Turnover, Debt to Asset Ratio, and Current Ratio on Price to Book Value with Return on Asset as an intervening variable in LQ45 companies listed on the Indonesia Stock Exchange in 2019 - 2023. The sample selection method used is purposive sampling. The total observations in this research were 115 samples with 5 years of observation consisting of 23 companies. The data analysis technique used in this research is moderation analysis using path analysis. The test results immediately show that Total Asset Turnover has a positive effect on Return on Assets, while Debt to Asset Ratio has a negative effect on Return on Assets, and Current Ratio has no effect on Return on Assets. The direct test results show that Total Asset Turnover and Debt to Asset Ratio have a positive effect on Price to Book Value, while Current Ratio has no effect on Price to Book Value. The overall test results show that Return on Assets is unable to mediate Total Asset Turnover, Debt to Asset Ratio, and Current Ratio on Price to Book Value.